Analisis Kemenangan Pasangan Calon Andra Soni dan Dimyati Natakusumah dalam Pilgub Banten 2024 - Iqbal, Ighasta Ahmad; Putriesli, Lamona; Salsabila, Nasywa; Putranto, Algooth (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The Andra-Dimyati pair built a large coalition with the support of ten political parties, demonstrating significant electoral strength in the Banten gubernatorial election. Their vision and mission, which focuses on